Ramsel Toledo - Thermocatalytic production of Synthetic Natural Gas from renewable carbon dioxide and hydrogen in a fluidized bed reactor with bifunctional solids (Jornada de Jóvenes Investigadores del I3A, 2025)
Thermocatalytic production of Synthetic Natural Gas from renewable carbon dioxide and hydrogen in a fluidized bed reactor with bifunctional solids.